ALGORITHMS FOR THE PROCESSES OF ESTABLISHING PRICES AND BALANCED BANK INTERESTS - CARINA-ELENA STEGĂROIU; VALENTIN STEGĂROIU (Annals of the University of Petrosani: Economics, 2010)
The paper proposed economic and mathematical models of processes for sale, purchase of resources, including financial ones, are analyzed (in mathematical language) economic indicators, financial industries preferred income, financial resources at the end of production are analyzed cases possible deployment of productive processes with and without recourse to bank loans, are useful to constructive conclusions national economy branches, including National Bank.